The Effectiveness of Discovery, Inquiry, Problem, and Project-Based Learning in Mathematics Education: A Systematic Literature Review - Lethulur, Nelma Dortje; Juandi, Dadang; Dahlan, Jarnawi Afgani (FKIP Universitas Lampung, 2025)
Discovery-based learning plays a crucial role in enhancing students' mathematical understanding and critical thinking skills. This study analyzes the implementation of four major models Discovery Learning, Inquiry-Based Learning (IBL), Problem-Based Learning (PBL), and Project-Based Learning (PjBL) through a Systematic Literature Review (SLR) of 52 Scopus-indexed studies. The findings indicate that these models effectively improve conceptual understanding, higher-order thinking skills, and student motivation. Data from TIMSS (Trends in International Mathematics and Science Study) 2019 and PISA (Programme for International Student Assessment) 2022 confirm that countries consistently implementing these models demonstrate superior mathematical performance. The integration of technology, such as GeoGebra and e-learning platforms, further enriches learning experiences and enhances instructional effectiveness. However, challenges remain, including time constraints, uneven understanding of implementation, and difficulties in assessment design. This study reaffirms that discovery-based learning is an appropriate approach for 21st-century mathematics education. Recommendations include increasing research at the primary and secondary education levels, exploring artificial intelligence-based learning technologies, and developing more effective assessment strategies to support the implementation of this model across diverse educational contexts. Keywords: discovery-based learning, mathematics education, systematic literature review.